PENYEMBUHAN HOLISTIK DALAM PERSPEKTIF GMIST SEBAGAI STRATEGI PASTORAL KONSELING BAGI PASIEN DI RUMAH SAKIT DAERAH LIUN KENDAGE TAHUNA - Pratiwi Anggraini Makansing; Olivia Cherly Wuwung; Yohan Brek (ATOHEMA: Jurnal Teologi Pastoral Konseling, 2024)
Holistic healing is a healing method that takes into account different aspects such as spiritual, social, in addition to medical and psychological aspects. Pastoral counseling helps the healing process holistically, more specifically the spiritual aspect of the human being. Liun Kendage Tahuna Regional Hospital has not realized how important holistic healing is for patients with pastoral counseling strategies. The method used in this study is a descriptive qualitative that seeks to describe a social phenomenon, where the data collected is first described, then analyzed and formulated. The purpose of this study is to show how important the role of pastoral counseling for patients is in realizing holistic healing from the perspective of GMIST.